A collection of transcriptomic and proteomic datasets from sesame in response to salt stress - Yujuan Zhang; Donghua Li; Rong Zhou; Aili Liu; Linhai Wang; Yanxin Zhang; Huihui Gong; Xiurong Zhang; Jun You (Data in Brief, 2020)
Soil salinity is a major abiotic factor affecting the growth and development of important crops such as sesame (Sesamum indicum L.). To understand the molecular mechanisms of this oilseed crop in response to salt stress, we examined the transcriptome and proteome profiles of two sesame varieties, with contrasting tolerances to salinity. Here, RNA sequencing and quantitative proteomic analyses of 30 samples from salt-tolerant and -sensitive sesame seedlings under salt stress were carried out. These data can be used for differential gene expression and protein accumulation analyses, based on a genetic aberration or phenotypic differences in sesame responses to salt stress. Our dataset provides an extensive resource for understanding the molecular mechanisms underlying the adaptation of sesame to salt stress, and may constitute useful a resource for increasing the tolerance of major crop plants to raised salinity levels in soils.